Day 2 Tue, October 27, 2020 2020
DOI: 10.2118/201834-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Carbonate Reservoirs: Effects of Fluid and Aging

Abstract: As the production of hydrocarbons from the carbonate reservoir increases, there is a necessity to enhance oil recovery methods to increase recovery factors and improve the economic efficiency of field development. The knowledge of wettability's role and fluid distribution at the pore scale is required to comprehend the mechanisms for oil displacement from porous media. The X-ray computed micro-CT technology provides opportunities to study the complex fluid displacement process at the pore level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Results indicated that carbonates in general require less aging time to alter their wettability condition to oil-wet, around 1–7 days, compared with sandstones, around 14–21 days, based on the temperature and oil used. It took 10–14 days to alter the wettability of carbonate rock samples with temperatures ranging between 25 and 90 °C. ,,,, On the contrary, it takes a longer duration ranging between 14 and 21 days at higher temperatures of 60–90 °C to change the rock sample wettability of sandstone. ,,,, …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results indicated that carbonates in general require less aging time to alter their wettability condition to oil-wet, around 1–7 days, compared with sandstones, around 14–21 days, based on the temperature and oil used. It took 10–14 days to alter the wettability of carbonate rock samples with temperatures ranging between 25 and 90 °C. ,,,, On the contrary, it takes a longer duration ranging between 14 and 21 days at higher temperatures of 60–90 °C to change the rock sample wettability of sandstone. ,,,, …”
Section: Discussionmentioning
confidence: 99%
“…It took 10–14 days to alter the wettability of carbonate rock samples with temperatures ranging between 25 and 90 °C. 32 , 33 , 36 , 37 , 46 48 On the contrary, it takes a longer duration ranging between 14 and 21 days at higher temperatures of 60–90 °C to change the rock sample wettability of sandstone. 33 , 40 , 42 , 45 , 49 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation